Aproveitamento energético da vinhaça de cana-de-açúcar pela biodigestão em dois estágios em reatores anaeróbios de leito fluidizado: mesofílico e termofílico - Ramos, Lucas Rodrigues (Universidade Federal de São Carlos, 2019)
This research evaluated the effect of operational parameters and of stage integration on the performance and energetic feasibility of the anaerobic digestion of sugarcane vinasse in anaerobic fluidized bed reactors. The research consisted of two studies. The first one investigated the effect of hydraulic retention time (HRT) (18 h to 10 h) on the CH4 production and organic load removal of the thermophilic (55 °C) methanogenic reactor of a two-stage digestion system. Based on these results, the second study evaluated the increase of organic loading rate (OLR) (2.7 a 24.7 kg COD.m-3.day-1) on thermophilic (55 °C) and mesophilic (30 °C) methanogenic reactors fed by the same acidogenic thermophilic reactor (55 °C). All systems were compared with single stage thermophilic digestors (55 °C). In addition to H2 (maximum yield of 0.70 ± 0.08 mmol H2.g COD-1 on the OLR of 90 kg COD.m-3.day-1), the higher production rates (MPR) were also observed on two-stage systems (2.71 ± 0.26 L CH4.day-1.L-1 to 3.18 ± 0.29 L CH4.day-1.L-1) on the OLR range of 13.3 to 21.6 kg COD.m-3.day-1, on thermophilic methanogenic reactors, and on the OLR of 24.7 kg COD.m-3.day-1 on the mesophilic reactor. Although the decrease in HRT was beneficial, the increase in OLR modified the performance of the methanogenic reactors in distinct ways. While the yield and the MPR of the thermophilic condition decreased by increasing the OLR to 24.7 kg COD.m-3.day-1, the MPR of the mesophilic reactor was maximum, indicating operational stability even under overload conditions. However, the higher MPR did not correspond to higher energy productions, especially on the thermophilic systems, being inferior to the single stage digester. The single stage system was estimated with 40567 m3 producing 28 MW (2.5 MW per million tons of sugarcane), with energy yield of 10850 kJ.kg CODrem-1. The best alternative to this system was the recycling of the effluent of the mesophilic metanogenic reactor to the feed of the thermophilic acidogenic reactor, designing an acidogenic reactor of 1424 m3 and a methanogenic reactor of 32,387 m3, producing 28.8 MW (2.6 MW per million tons of sugarcane) with an energy yield of 10777 kJ.kg CODrem-1. Thus, energetic recovery of sugarcane vinasse by biodigestion on anaerobic fluidized bed reactors is recommended on two-stage systems with a thermophilic acidogenic reactor (OLR 90 kg COD.m-3.day-1) and a mesophilic metanogenic reactor (OLR 8 kg COD.m-3.day-1).
Harnessing bioenergy from sugarcane vinasse by biodigestion in two-stage anaerobic fluidized bed reactors: mesophilic and thermophilic conditions
Keywords: Biohidrogênio; Biometano; Carga orgânica; Viabilidade energética; Estimativa de aumento de escala; Biohydrogen; Biomethane; Organic load; Energetic feasibility; Scale-up estimation; ENGENHARIAS::ENGENHARIA QUIMICA